Lead phosphate deposition in porous media and implications for lead remediation. (1st May 2022) - Zhao, Juntao; Mowla, Marfua; Pan, Zezhen; Bao, Daniel; Giammar, Daniel E.; Hu, Yandi; Louie, Stacey M.
Highlights: The breakthrough of lead phosphate particles in sand columns was investigated. Attachment in NaNO3 was influenced by ripening, straining, and weak deposition. Low P/Pb ratios enhanced the aggregation and deposition of lead phosphate particles. Ca 2+ promoted the aggregation and deposition of lead phosphate particles. Humic acid enhanced the mobility of lead phosphate particles in porous media. Abstract: Phosphate addition is commonly applied as an effective method to remediate lead contaminated sites via formation of low solubility lead phosphate solids. However, subsequent transport of the lead phosphate particles may impact the effectiveness of this remediation strategy. Hence, this study investigates the mechanisms involved in the aggregation of lead phosphate particles and their deposition in sand columns as a function of typical water chemistry parameters. Clean bed filtration theory was evaluated to predict the particle deposition behavior, using Derjaguin–Landau–Verwey–Overbeek (DLVO) theory to estimate particle-substrate interactions. The observed particle deposition was not predictable from the primary energy barrier in clean bed filtration models, even in simple monovalent background electrolyte (NaNO3 ), because weak deposition in a secondary energy minimum prevailed even at low ionic strength, and ripening occurred at ionic strengths of 12.5 mM or higher. For aged (aggregated) suspensions, straining also occurred at 12.5 mM or higher. Aggregation and deposition were further enhanced at low total P/Pb ratios (i.e., P/Pb = 1) and in the presence of divalent cations, such as Ca 2+ (≥ 0.2 mM), which resulted in less negative particle surface potentials and weaker electrostatic repulsion forces. However, the presence of 5 mg C/L of humic acid induced strong steric or electrosteric repulsion, which hindered particle aggregation and deposition even in the presence of Ca 2+ . This study demonstrates the importance of myriad mechanisms in lead phosphate deposition and provides useful information for controlling water chemistry in phosphate applications for lead remediation. Graphical abstract: Image, graphical abstract